Fungsi Badan Permusyawaratan Desa (BPD) Dalam Mewujudkan Pemerintahan Desa Berdasarkan Prinsip Tata Kelola Pemerintahan Yang Baik: (Studi di Kecamatan Pujut, Lombok Tengah) - Suryanata, Lalu Aang; Rusnan, Rusnan; Koynja, Johannes Johny (Bagian Hukum Tata Negara Fakultas Hukum, Ilmu Sosial, dan Ilmu Politik Universitas Mataram, 2023)
This study points out main duties of village representative boards in Pujut Sub-District and identifies factors hampering good governance principles from being implemented in village governance. This is an empirical study with statutory, conceptual, sociological, and comparative approaches. The study was conducted in Mertak, Kuta, and Sukadana Villages. Results of this study show that main duties of village representative board according to Article 55 of the Law No. 6 of 2014 of Village are, firstly, discussing and establishing village regulation along with the head of village. Secondly, accommodating and conveying village community’s aspirations. Lastly, supervising head of village performance. In addition, there are differences in perspectives and approaches of those three villages in putting good governance principles into practice. According to this study, village representative boards of the three villages are highly likely to have made efforts in implementing the good governance principles respectively. Despite both participation and accountability principles are still inadequately implemented in Mertak and Sukadana villages. Whereas in Kuta Village, the overall principles’ implementation is relatively satisfactory in all three the Village Representative Board’s main duties. In addition, factors hampering village representative boards from implementing good governance principles are, inadequate human resource quality, the absence of Supervision Committee, and the lack of facilities for the board members.